The legal action and the amendment of conscience in Portugal during the Age of the Avis Dynasty - Teodoro, Leandro Alves [UNESP] (FapUNIFESP (SciELO), 2024)
In Portugal on the threshold of the 15th century, the Avis dynasty intensified the reform of customs not only within the court but also in various regions with the aim of establishing Christian parameters of conduct valid for nobles and other men. This was a policy reinforced by the actions of bishops interested in establishing criteria for action for clergy and laity based on constitutions promulgated in reformist synods. By juxtaposing impressions of members of the House of Avis with prescriptions of bishops, this article aims to examine the complementarity of monarchic and ecclesiastical actions in strengthening the inner forum, highlighting the authors of the first goal of the fifteenth century and the repercussions of their debates in works of the following decades. In other words, the aim is to analyze the power dynamics that defined the spaces for the amendment of conscience in the Portuguese kingdom of the fifteenth century.
A ação jurídica e a emenda da consciência no Portugal dos Avis
Keywords: 15th century; Portugal; Reform